(untitled) (Altre Modernità, 2025)
La giovinezza di Giulio Cesare is Giuseppe Rovani’s last novel. Strongly appreciated by contemporary critics, it did not arouse great interest in twentieth-century critics. The text, however, which fits coherently into the long historical narrative of the Milanese author, presents some important characteristics, which suggest a true conclusion of the author’s creative laboratory. The interest in the narrative of youth and the archaeological-artistic ambition―already present in his previous novels―reappear here in the light of the character considered the most complete expression of human genius and in a foundational space and time in the past.